Movement, resources, interaction (Turnhout, Belgium)
xi, 257 sayfa
Keywords: “This second volume in a series of publications of the Kültepe International Meetings collects sixteen papers on the Anatolian and Syrian Bronze Age read at the Second Kültepe International Meeting in July of 2015. It anchors the site in the dimensions of time and space by bringing together specialists to present studies on the effects of commercial and cultural interaction in a broad chronological and geographical perspective. Focus is on the period 2500-1600 BCE when Central Anatolia was divided into dozens of densely populated microstates, each centred on an individual urban and palatial institution, but connected through a shared linguistic, material and religious horizon. Tying together this competitive system of peer polities was also a complex network of commercial exchange operated by local and foreign merchants working in and beyond the region. The site of Kültepe provides the best documentation for this international network through a unique convergence of textual, physical and scientific data. This allows volume authors to extrapolate beyond the confines of the site itself to explore some of the foundational technological, commercial, cultural and biological connections that spanned the Eurasian landmass in the Bronze Age under the headings 'Movement, Resources, Interaction” --